OPTIMALISASI PERSEDIAAN MAKANAN TERNAK PADA PT. MARGO SANTOSA DI SANGATTA - Elfreda Aplonia Lau, Reynold Osmon, LCA. Robin Jonathan (EKONOMIA, 2015)
Problem Formulation Are Stocks Feed the planned PT. Margo Santosa in Sengata Already Optimal. The purpose of research to determine and calculate the optimal supply of food animals at PT. Margo Santosa in Sangatta. theory used in this study and Management Operations Management Persediaan.Data used are secondary data obtained from PT.Margo Santosa in Sangatta.Adapun hypothesis put forward Inventory Feed on PT. Margo Santosa in Sengata not optimal. Analysis of optimization of computer supplies, used the model analysis tools Economic Order Quantity (EOQ), with the following procedures: 1) . optimal inventory number 2) . storage costs per year 3) . total cost per year 4) . booking fee per year 5) calculate Safety Stock. Thus Hypothesis which states that the planned inventory Fodder PT Margo Santosa Sengata proven not optimal and acceptable